2018
DOI: 10.1128/aem.00086-18
|View full text |Cite
|
Sign up to set email alerts
|

Thioredoxin and Glutaredoxin Systems Required for Oxidative Stress Resistance, Fungicide Sensitivity, and Virulence of Alternaria alternata

Abstract: This study determined the function of thioredoxin and glutaredoxin systems in the phytopathogenic fungus via analyzing mutants obtained from the targeted deletion of genes encoding thioredoxin peroxidase (), thioredoxin reductase (), and glutathione reductase (). and, but not , are required for growth and conidiation. The reduced growth and conidiation seen in the or deletion mutant can be restored by glutathione. Deletion mutants showing growth inhibition by oxidants are defective for HO detoxification and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
63
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(64 citation statements)
references
References 54 publications
1
63
0
Order By: Relevance
“…The mechanisms underlying ROS resistance have been studied in A. alternata . Previous research has suggested that the NADPH oxidase complex generates low‐level H 2 O 2 that acts as a secondary signal to promote the nuclear translocation of Yap1 and Hog1, and to activate the expression of the genes encoding Yap1, Skn7, and Hog1, which in turn activate the thioredoxin ( AaTsa1 and AaTrr1 ) and glutaredoxin ( AaGpx3 and AaGlr1 ) systems in response to oxidative damage (Ma et al ., 2018). In the present study, RT‐qPCR revealed that the expression of AaTrr1 , AaGpx3 , and AaGlr1 was significantly down‐regulated in Δ Aatfb5 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanisms underlying ROS resistance have been studied in A. alternata . Previous research has suggested that the NADPH oxidase complex generates low‐level H 2 O 2 that acts as a secondary signal to promote the nuclear translocation of Yap1 and Hog1, and to activate the expression of the genes encoding Yap1, Skn7, and Hog1, which in turn activate the thioredoxin ( AaTsa1 and AaTrr1 ) and glutaredoxin ( AaGpx3 and AaGlr1 ) systems in response to oxidative damage (Ma et al ., 2018). In the present study, RT‐qPCR revealed that the expression of AaTrr1 , AaGpx3 , and AaGlr1 was significantly down‐regulated in Δ Aatfb5 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, A. alternata has to cope with toxic reactive oxygen species (ROS) in order to gain successful colonization in citrus leaves. Several proteins, including the NADPH oxidase (Yang and Chung, 2013), the redox‐responsive transcription factor Yap1 (Lin et al ., 2009), the mitogen‐activated protein (MAP) kinase Hog1 (Lin and Chung, 2010), the stress response regulator Skn7 (Chen et al ., 2012), and proteins in the thioredoxin and glutaredoxin systems (Ma et al ., 2018), have been demonstrated to be required for resistance to ROS and full virulence of A. alternata on citrus. It has been hypothesized that H 2 O 2 generated by the NADPH oxidase complex acts as a secondary messenger to activate the expression of Yap1 and Hog1 , which activate both thioredoxin and glutaredoxin systems for ROS detoxification (Ma et al ., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The filamentous fungal insect pathogen B. bassiana also contains two TrxRs that play distinct roles in the redox system and host infection (Zhang et al, 2016). However, only one TrxR was identified in fungal plant pathogens, including B. cinerea , M. oryzae , and A. alternata , and a cytoplasmic location was demonstrated in these fungi (Fernandez and Wilson, 2014; Viefhues et al, 2014; Ma et al, 2018). BLASTP searches indicated that S. sclerotiorum contains only one TrxR-encoding gene, and this number is consistency with other fungal plant pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…A loss of TrxR in Magnaporthe oryzae resulted in strains that failed to produce spreading necrotic lesions on the leaf surface (Fernandez and Wilson, 2014). The targeted deletion of TrxR in Alternaria alternata led to strains that were defective in H 2 O 2 detoxification and induced smaller lesions on citrus leaves (Ma et al, 2018). In Botrytis cinerea , a fungus closely related to S. sclerotiorum , deletion of the TrxR-encoding gene, trr1 , impaired fungal virulence and antioxidant capabilities (Viefhues et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…A low level of H 2 O 2 generated by the NADPH oxidase (Nox) likely activates Yap1, Hog1, and Skn7 at transcriptional and/or post-translational levels, which could subsequently enhance siderophore biosynthesis foriron uptake and storage and promote antioxidant activities including superoxide dismutase (SOD), catalase, and peroxidase,all leading to oxidative stress resistance ( Chen et al, 2013 , 2014 ). Yap1, Hog1, and Skn7 could also activate gluataredoxin and thioredoxin systems to cope with oxidative stress ( Yang et al, 2016 ; Ma et al, 2018 ). Because H 2 O 2 is toxic to cells, Yap1, Hog1, and Skn7 would suppress the expression of the Nox genes (transcriptional feedback inhibition) to avoid the unrestraint production of H 2 O 2 .…”
Section: Discussionmentioning
confidence: 99%